The Influence of Communication in the Buyer-Supplier Integration on Procurement Performance of Large Manufacturing Firms in Tanzania - Kimario, Honest Fidelis; Mwagike, Leonada R (International Journal of Supply Chain Management, 2021)
Despite the efficacious communication evident in the buyer-supplier relationship, material procurement performance in large manufacturing firms of Tanzania remains a challenge. The Resources Dependency and Transaction Cost Economics Theories were used in this study to analyze the influence of Early Supplier Involvement in design specification, electronic information sharing, communication direction, and frequency of buyer-supplier meetings,(all considered key in enhancing communication in the buyer-supplier relationship), on procurement performance. 52 large manufacturing firms in Temeke Municipality were approached through a census to inform the study. From each firm, one procurement and one store manager were purposively sampled, totaling to 104 respondents. Data was obtained through questionnaires and analyzed using the Binary logistic regression. This study was supplemented by qualitative opinions since communication in the buyer-supplier relationship is a strategic aspect. The study revealed that poor procurement performance is attributed to lack of Early Supplier Involvement and limited electronic information sharing. It was recommended as per findings that with the assistance of the government, a framework should be developed and adopted by manufacturing firms so as to address procurement performance drawbacks. Future studies should grasp the mediating role of third-party logistics on the influence of communication in the buyer-supplier relationship on procurement performance of large manufacturing firms in Tanzania.